Modelling individual differences in reading using an optimised MikeNet simulator: the impact of reading instruction - Chang, Ya-Ning; Chang, Ting-Jung; Lin, Wei-Fen; Kuo, Ching-En; Shi, Yu-Ting; Lee, Hung-Wei (Frontiers in Human Neuroscience, 2024)
Reading is vital for acquiring knowledge and studies have demonstrated that phonologyfocused interventions generally yield greater improvements than meaning-focused interventions in English among children with reading disabilities. However, the effectiveness of reading instruction can vary among individuals. Among the various factors that impact reading skills like reading exposure and oral language skills, reading instruction is critical in facilitating children's development into skilled readers; it can significantly influence reading strategies, and contribute to individual differences in reading. To investigate this assumption, we developed a computational model of reading with an optimised MikeNet simulator. In keeping with educational practices, the model underwent training with three different instructional methods: phonology-focused training, meaning-focused training, and phonology-meaning balanced training. We used semantic reliance (SR), a measure of the relative reliance on print-to-sound and print-to-meaning mappings under the different training conditions in the model, as an indicator of individual differences in reading. The simulation results demonstrated a direct link between SR levels and the type of reading instruction.Additionally, the SR scores were able to predict model performance in reading-aloud tasks: higher SR scores were correlated with increased phonological errors and reduced phonological activation. These findings are consistent with data from both behavioural and neuroimaging studies and offer insights into the impact of instructional methods on reading behaviours, while revealing individual differences in reading and the importance of integrating OP and OS instruction approaches for beginning readers.